Acidithiobacillus ferrooxidans improved H2S gas sensing properties of tubular hydroxyapatite at room temperature. Issue 80 (15th August 2016) - Tan, Yanni; Li, Huixia; Liu, Yong; Xie, Jianping; He, Jia; Pan, Jun
Abstract : H2 S gas sensing properties of HAp was significantly improved by mixing with Acidithiobacillus ferrooxidans . Abstract : A novel H2 S gas sensing composite based on tubular hydroxyapatite (HAp) and Acidithiobacillus ferrooxidans ( At.f ) was prepared, and the gas sensing properties of pure HAp and the composite to H2 S were studied. The microstructures, crystalline phases and chemical groups of the composites were characterized by SEM, TEM, XRD, and FTIR. Results show that jarosite was formed during the cultivation of At.f . Compared to pure HAp, the composite exhibited a more excellent response to H2 S. With the increase of the amount of Acidithiobacillus ferrooxidans added, the sensitivity of the composite to H2 S increased. The composite showed a highest sensitivity of 76% to H2 S at 2000 ppm, which is 2.5 times that of pure HAp. The probable sensing mechanisms of the composite to H2 S were proposed. Other than the At.f, the structure and the chemical groups of jarosite are also beneficial for H2 S gas sensing.